Tillgång till offentligheten: synlikhet och rörlikhet - Muslimska kvinnors religiösa aktivism i Istanbul - Raudvere, Catharina (Kvinder, Køn & Forskning, 2000)
The article discusses muslim women and religious practices in Istanbul, Turkey. By using theories of globalization and the post-modern society, the author analyzes the possibilities in the politization of Islam for the active Muslim women as a way to become part of the social development.